Consumption of industrial processed foods and risk of premenopausal breast cancer among Latin American women: the PRECAMA study. Issue 1 (4th January 2022) - Romieu, Isabelle; Khandpur, Neha; Katsikari, Aikaterini; Biessy, Carine; Torres-Mejía, Gabriela; Ángeles-Llerenas, Angélica; Alvarado-Cabrero, Isabel; Sánchez, Gloria Inés; Maldonado, Maria Elena; Porras, Carolina; Rodriguez, Ana Cecilia; Garmendia, Maria Luisa; et al.
Abstract : Ultra-processed food intake has been linked to an increased risk of breast cancer in Western populations. No data are available in the Latin American population although the consumption of ultra-processed foods is increasing rapidly in this region. We evaluated the association of ultra-processed food intake to breast cancer risk in a case–control study including 525 cases (women aged 20–45 years) and 525 matched population-based controls from Chile, Colombia, Costa Rica and Mexico. The degree of processing of foods was classified according to the NOVA classification. Overall, the major contributors to ultra-processed food intake were ready-to-eat/heat foods (18.2%), cakes and desserts (16.7%), carbonated and industrial fruit juice beverages (16.7%), breakfast cereals (12.9%), sausages and reconstituted meat products (12.1%), industrial bread (6.1%), dairy products and derivatives (7.6%) and package savoury snacks (6.1%). Ultra-processed food intake was positively associated with the risk of breast cancer in adjusted models (OR T3-T1 =1.93; 95% CI=1.11 to 3.35). Specifically, a higher risk was observed with oestrogen receptor positive breast cancer (ORT3-T1 =2.44, (95% CI=1.01 to 5.90, P-trend=0.049), while no significant association was observed with oestrogen receptor negative breast cancer (ORT3-T1 =1.87, 95% CI=0.43 to 8.13, P-trend=0.36). Our findings suggest that the consumption of ultra-processed foods might increase the risk of breast cancer in young women in Latin America. Further studies should confirm these findings and disentangle specific mechanisms relating ultra-processed food intake and carcinogenic processes in the breast.